TRACING THE EVOLUTIONARY PHASES OF PASSENGER CAR SUPPLY SYSTEMS: A RESEARCH INQUIRY - Otaboyev Nodirbek Ibragimovich (European Science Publishing, 2023)
In this article, the results of the research on the changes in the technical conditions of car tires during operation and the extension of safety and service life by managing their resources are highlighted. It is also recommended to ensure the flexibility and durability of tires in different climatic conditions and to control the pressure inside them. This research endeavour examines the evolutionary trajectory of supply systems concerning passenger cars. It systematically investigates the developmental stages that have shaped the provisioning and distribution mechanisms within the passenger car industry. Through a comprehensive analysis, this study delves into the historical, economic, and logistical aspects contributing to the evolution of these supply systems. It explores key milestones, transformations, and influential factors that have shaped the procurement, distribution, and availability of passenger vehicles over time. By mapping these developmental stages, the research aims to offer insights into the industry's growth patterns, technological advancements, market dynamics, and the impact of regulatory frameworks. This exploration intends to provide a nuanced understanding of the complex interplay between various factors that have influenced the supply chains of passenger cars, facilitating informed strategies for future enhancements and adaptations within this sector.
Keywords: Passenger Car Industry, Supply Systems, Evolutionary Phases, Developmental Stages, Transportation History, Manufacturing Logistics, Consumer Behavior, Historical Analysis, Economic Perspectives, Logistical Evolution, Market Dynamics.